Trusted Computing: An Elusive Goal. - Michael, James Bret (Computer (00189162), 2015)
Recent high-profile cyberattacks such as the massive data leak at Sony leave us wondering where such lack of trustworthiness will take us. The answer, of course, is nowhere we want to go.